Experimental and computational investigation of polylactic acid/silver‐NP nanocomposite with antimicrobial activity prepared by plasma in liquid. Issue 2 (26th October 2020) - Sirotkin, Nikolay A.; Gurina, Darya L.; Khlyustova, Anna V.; Costerin, Dmitry Yu.; Naumova, Irina K.; Titov, Valeriy A.; Agafonov, Alexander V.
Abstract : We investigated a one‐step method for creating composite polymer materials containing silver nanoparticles (AgNPs). An underwater impulse discharge initiated between silver electrodes placed in a water suspension of dissolved PLA is applied to produce AgNPs and incorporate them into the polylactide matrix. We observed a strong antimicrobial activity of PLA/AgNPs films against Gram‐negative bacteria, Gram‐positive bacteria, and yeasts Abstract: In this study, an underwater impulse discharge initiated in an aqueous suspension of a polylactide acid between silver rods is applied to produce silver nanoparticles (AgNPs) and create a polymer nanocomposite. The spectral and energy characteristics of the discharge are obtained. The composites are characterized by methods of scanning electron microscopy, transmission electron microscopy, infrared spectroscopy, and thermogravimetric analysis. Investigation of the formation of the composite of polylactic acid (PLA) with AgNP has been performed using the molecular dynamics method. The PLA/AgNPs composite films were effective against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Candida albicans, and thus may find future application in the food packaging area.